2015
DOI: 10.1586/17434440.2015.1050378
|View full text |Cite
|
Sign up to set email alerts
|

Wear testing of total hip replacements under severe conditions

Abstract: Controlled wear testing of total hip replacements in hip joint simulators is a well-established and powerful method, giving an extensive prediction of the long-term clinical performance. To understand the wear behavior of a bearing and its limits under in vivo conditions, testing scenarios should be designed as physiologically as possible. Currently, the ISO standard protocol 14242 is the most common preclinical testing procedure for total hip replacements, based on a simplified gait cycle for normal walking c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 126 publications
1
6
0
Order By: Relevance
“…Despite the optimistic expectations for their in vivo performance and the positive data collected by in vitro simulation according to the ISO standard protocol 14242 (Kyomoto et al, 2007(Kyomoto et al, , 2017Moro et al, 2004;Takatori et al, 2015), the MPC-graft disappeared from the bearing surface due to frictional forces or environmental conditions (i.e., even in NWZs). This output confirmed that the in vivo environment represents a much more severe testing workbench as compared to in vitro predictions (Zietz et al, 2015). Despite the low amount of wear damage found in all the short-term retrievals investigated (cf., Figure 1), XPS and ATR-FTIR analyses consistently showed significant differences in oxygen contents between pristine and in vivo exposed liners (cf., Tables 2 and 3 intensity.…”
Section: Discussionsupporting
confidence: 74%
“…Despite the optimistic expectations for their in vivo performance and the positive data collected by in vitro simulation according to the ISO standard protocol 14242 (Kyomoto et al, 2007(Kyomoto et al, , 2017Moro et al, 2004;Takatori et al, 2015), the MPC-graft disappeared from the bearing surface due to frictional forces or environmental conditions (i.e., even in NWZs). This output confirmed that the in vivo environment represents a much more severe testing workbench as compared to in vitro predictions (Zietz et al, 2015). Despite the low amount of wear damage found in all the short-term retrievals investigated (cf., Figure 1), XPS and ATR-FTIR analyses consistently showed significant differences in oxygen contents between pristine and in vivo exposed liners (cf., Tables 2 and 3 intensity.…”
Section: Discussionsupporting
confidence: 74%
“…Higher posterior loads throughout the weight-bearing phase of the activity characterize stair descent when compared to other locomotive activities, and these would be expected to alter the 3-dimensional loading pattern at the bearing surface and potentially lead to different wear behavior. These differences are profound when comparing individual activities and they could potentially be magnified when considering the much greater variety of activities that the wider THA population engages in [40,41]. Including contrived ADLs or adverse loading conditions in preclinical wear tests has previously produced higher levels of wear [42,43], and the interaction between patient kinematics and surgical factors such as cup placement [44] wear is a multifactorial phenomenon.…”
Section: Discussionmentioning
confidence: 99%
“…However, there are some problems with Caravia's experiment. It was reported that the sedimentation of particles could influence the testing result [89]. Nowadays, two methods are proposed to solve the precipitation of hard particles.…”
Section: Hard Particlesmentioning
confidence: 99%